Quadriceps or triceps surae proprioceptive neuromuscular facilitation stretching with post-stretching dynamic activities does not induce acute changes in running economy - Konrad, A.; Tilp, M.; Stöcker, F.; Mehmeti, L.; Mahnič, N.; Seiberl, W.; Behm, D. G.; Paternoster, F. K. (Frontiers in Physiology, 2022)
Previous studies reported that both a more compliant quadriceps tendon and a stiffer Achilles tendon are associated with better running economy. While tendon stiffness can be decreased by a single bout of proprioceptive neuromuscular facilitation (PNF), post-stretching dynamic activities (PSA) can counteract the potential stretch-induced force loss. Thus, the purpose of this study was to investigate if a single, moderate duration, (4x15 s), bout of PNF stretching of either the quadriceps or triceps surae muscles followed each by PSA, causes either an improvement or impairment in running economy. Eighteen trained male runners/triathletes visited the laboratory five times. The first two visits were to familiarize the participants and to test for maximal oxygen consumption (VO2max) respectively. The further three appointments were randomly assigned to either 1.) quadriceps PNF stretching +PSA or 2.) triceps surae PNF stretching +PSA or 3.) no stretching +PSA. Following the interventions, participants performed a 15-min run on the treadmill with a speed reflecting a velocity of 70% VO2max to assess oxygen consumption (i.e., running economy) and running biomechanics. Our results showed neither a difference in oxygen consumption (P=0.15) nor a change in any variable of the running biomechanics (P>0.33) during the steady-state (i.e., last five minutes) of the 15-min run. Athletes can perform moderate duration PNF stretching of the quadriceps or triceps surae + PSA prior to a running event, without affecting running economy. Future studies should emphasize long-term training effects on tendon stiffness adaptations and running economy.